2003
DOI: 10.1002/esp.494
|View full text |Cite
|
Sign up to set email alerts
|

Rock thermal data at the grain scale: applicability to granular disintegration in cold environments

Abstract: Consideration of the mechanisms associated with the granular disintegration of rock has been limited by available data. In most instances, both the size of the transducer and the nature of the study have negated any applicability of the resulting data to the understanding of grain-to-grain separation within rock. The application of microthermocouples (≤0·15 mm diameter) and high-frequency logging (20 s intervals) at a taffoni site on southern Alexander Island and from a rock outcrop on Adelaide Island (Antarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 35 publications
2
75
0
2
Order By: Relevance
“…McKay et al (2009) and Hall and André (2003) noted that > 1 measurement per minute temporal resolution of data may provide key insights into fracturing processes and the data acquisition system described herein was able to achieve that sampling frequency.…”
Section: Data Acquisition Configurationmentioning
confidence: 94%
See 2 more Smart Citations
“…McKay et al (2009) and Hall and André (2003) noted that > 1 measurement per minute temporal resolution of data may provide key insights into fracturing processes and the data acquisition system described herein was able to achieve that sampling frequency.…”
Section: Data Acquisition Configurationmentioning
confidence: 94%
“…Instrumentation studies of diurnal variations in rock surface strain and/or temperature (while somewhat more common) have been limited to relatively short monitoring periods consisting of only one or two days (e.g., Hall and André, 2003;McKay et al, 2009); long periods between individual measurements (e.g., Wegmann and Gudmunson, 1999;Viles, 2005;McFadden et al, 2005), and/or only a single sensor per rock (e.g., Viles and Goudie, 2007). A long-term, multi-sensor study with high temporal and spatial measurements of temperature, strain, moisture, and acoustic emissions is unprecedented, but necessary to capture natural, spatial and temporal patterns of pertinent rock surface and environmental conditions that are associated with fracturing.…”
Section: K Warren Et Al: Automated Field Detection Of Rock Fracturimentioning
confidence: 99%
See 1 more Smart Citation
“…Insolation is a potential weathering agent due to the stress generated as a result of temperature differences (Rice 1976;Smith, 1977, Hall andAndré, 2003;Gomez-Heras et al, 2006, 2008Riley et al, 2012). In heterogeneous rock such as granite, the quartz and feldspar crystals have different thermal expansion coefficients and consequently react differently to weathering.…”
Section: Polygonal Cracking: Origin and Descriptionmentioning
confidence: 99%
“…In a series of papers that have similarly used high-frequency monitoring of surface temperatures, they established that rocks in these areas can likewise experience rapid temperature fluctuations (Hall and Andre, 2001). They have also demonstrated that these fluctuations and associated stresses are particularly manifest at the microscale, where frequent differential expansion is driven by thermal and crystallographic mismatches between crystals and grains (Hall and Andre, 2003). In this way, thermal stress fatigue failure (Hall, 1999) could occur where individual thermally induced stress events are insufficient to cause immediate failure but, collectively over time, can cause a material to fail.…”
Section: Paper Inmentioning
confidence: 99%